Implementasi Search Engine Optimization (SEO) pada Sistem Informasi E-Commerce menggunakan Plugin Wordpress (Studi Kasus Toko Online Norilyascake) - Rizkina Arya Nurfadilla; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Norilyascake is a food business that was founded in 2017 with the business of producing and selling birthday cakes that serve customers with a business to consumer business model. Along with the development of technology, Norilyascake wants to maximize their marketing, especially on search engines as a form of taking advantage of technological developments. Currently, norilyascake has implemented their marketing via Instagram. However, SEO optimization cannot be done because Norilyascake does not have a website or page. So, this research begins with creating a website using Wordpress, using the address https://norilyascake.com. After creating the website, it is then continued with on-page and off-page Search Engine Optimization (SEO) optimization by utilizing the Yoast SEO, Elementor and Fast Velocity Minify plugins on WordPress. The method used is research and development or implementative. This is to test the effectiveness of the implementation of on-page SEO and off-page SEO in terms of performance, the number of visitors and the ranking of the norilyascake.com website on the Google search engine. Based on the results of website analysis, on-page SEO analysis, off-page SEO analysis and competitors, with Who.is, Yoast SEO, Elementor and Fast Velocity Minify it can be seen that norilyascake.com requires optimization of on-page SEO and off-page SEO to align norilyascake.com with Google's algorithm rules to compete with websites that are at the 10th rank of Google SERP. In addition, after the analysis is done, the author will implement on-page SEO and off-page SEO on norilyascake.com. Based on the results of the test, there is an increase in performance, visitors, and search engine rankings. Improved performance from 1 query, 22 impressions and 5 clicks to 19 queries, 295 impressions and 43 clicks. Visitors also experienced an increase, with the highest total being 92 visitors with a percentage of 80% new visitors and 20% returning visitors. There is also an increase in the SEO authority score. Moz's Domain Authority increased five points from 0 to 5. Meanwhile, Ahrefs's Domain Rating increased seven points from 0 to 7.